Reconstructing the past : history of municipality, city, and provincial libraries in the province of Rizal from 1951 to 2018 - Guilles, Dennis Marco T.; Obille, Kathleen Lourdes B.; Cabbab, Johann Frederick A.; Golfo, Mary Grace P.; Lagrama, Eimee Rhea, C.; Silverio, Rochelle S. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
This study focused on the narrative description of historical facts, formulated acceptable interpretations, and established clear connections of what happened in the past based on factual and concrete evidence, to better understand the present conditions of public libraries in Rizal province. Arguably, if librarians were able to fully understand their libraries' present conditions, then they would be able to make informed decisions and execute action plans towards growth and development of their respective libraries.

A total of 11 affiliated public libraries in the province of Rizal were identified from the National Library of the Philippine's website. Nine municipal libraries (Angono, Baras, Binangonan, Cainta, Cardona, Jala-Jala, Rodriguez, San Mateo, and Taytay), one city library (Antipolo), and one provincial library (Rizal) were the subjects of this study. Primary and secondary sources of information regarding the municipal, city, and provincial libraries in Rizal province were searched, reviewed, and analyzed in this study.

Due to the absence of historical records, tracking the growth and development of most subject libraries in this study posed a great challenge. Library services, utilization of library resources, and users' statistics, were greatly affected by the following: absence of a qualified librarian to supervise the library, renovations conducted, transferring to a new location, accessibility of the library to the community, non-library related activities administered in the library, and insufficient number of library resources and facilities to cater to the information needs of the community.

Public libraries in Rizal province went through periods of growth, maturity, and decline. Periods of decline were evident through uncontrollable events such as the fire incident that hit Antipolo City Library and extreme flooding caused by typhoon "Ondoy" in Angono Municipal Library. Understanding all these experiences would enable librarians to make informed decisions, which would affect the services that they provide to the community.
Keywords: Public libraries -- Rizal, Philippines